Clinical phase II study of pegylated liposomal doxorubicin as second-line treatment in disseminated melanoma - Fink, Wolfram; Figl, Adina; Figl, Robert; Ugurel, Selma; Schadendorf, Dirk (Onkologie, 2004)
Background: Stage IV melanoma has a poor prognosis with a median survival of 3-11 months from diagnosis of distant metastases. Response rates in first-line regimens range around 15-20%. Non-responders have a median survival around 6 months. Currently, no second-line treatment in advanced melanoma has been established. Patients and Methods: In a clinical phase II study we evaluated the efficacy of liposomal doxorubicin (Caelyx?) in 30 patients (17 m, 13 f) with progressing metastatic melanoma who had failed a previous chemotherapy. Liposomal doxorubicin was given in an outpatient setting at a dose of 50 mg/m2 i.v. on d1, d22, d43 and d64, subsequently at 40 mg/m2 at d85 before first staging and in 4-week intervals thereafter. Treatment was very well tolerated with 100 cycles given in total. Response rate, survival time, time-to-progression and toxicity were assessed. Results: Erythrodysesthesia was the most severe toxicity in 6% at CTC grade 3. Liposomal doxorubicin was of limited clinical efficacy with 21 patients progressing within the first 12 weeks. However, 7 patients were treated 3-9 months and were stable for >90 days, achieving 5 SD, 1 PR and 1 CR. Median survival after initiation of second-line treatment was 214 days (95% CI: 151-304 days) with 7 patients surviving >300 and 5 patients >400 days. Conclusions: Liposomal doxorubin as monotherapy is well tolerated but of limited clinical efficacy. Whether the survival benefit of a significant proportion of patients (20%) holds true in larger cohorts and whether the efficacy of liposomal doxorubicin can be improved by combinations without compromising the low toxicity profile needs further studies.